Handbook of research on fuzzy and rough set theory in organizational decision making - Sangaiah, Arun Kumar; Gao, Xiao-Zhi; Abraham, Ajith 1968- (Business Science Reference, 2017)
"This book presents both empirical and applied research in the field of fuzzy set theory, and bridges the gap between the application of soft computational approaches and the organizational decision making process"--
Literaturverzeichnis Seite 434-465
Keywords: Decision making / Mathematical models; Fuzzy sets; Mathematisches Modell; Entscheidung; Fuzzy-Menge; Organisation